ANALYSIS OF CONTAINER CRANE ON STEVEDORING AT NILAM MULTIPURPOSE TERMINAL - Mudayat Mudayat; Soedarmanto Soedarmanto; Meyti hanna ester kalangi; Fina idatul umah (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This study is titled "Analysis of Container Cranes on Stevedoring in Nilam Multipurpose Terminals The Use of Container Crane Against Container Stevedoring in Nilam Multipurpose Terminals". This study aims to determine the effect of using a Container Crane on the productivity of container stevedoring activities at Nilam multipurpose terminals. Design/methodology/approach: This study uses a descriptive method with a qualitative approach accompanied by other instruments such as secondary data, interviews and documentation which aims to determine the influence of container crane loading and unloading productivity and also supporting factors that can maximize the performance of the container crane at the Nilam Multipurpose Terminal. The data used as analytical material to support the research is performance data from loading and unloading activities at the Nunukan Island KM in 2016 to 2017 in the first semester Findings: The results showed that the role of container cranes is the most important factor in the implementation of container loading and unloading activities at Nilam multiplepurpose terminals. Keywords: Container Crane, Stevedoring, Container